SISTEM PAKAR UNTUK TINDAK LANJUT PELANGGARAN SISWA DENGAN MENGGUNAKAN METODE FORWARD CHAINING (STUDI KASUS : SMP NEGERI 17 SURABAYA) - Dian Aprianto; Achmad Zakki Falani (Program Studi Teknologi Informasi, 2020)
Violations are noncompliance or intentional forms of bad behavior and students' lack of discipline in carrying out the rules that have been applied in schools. Lots of students who act on their own accord and commit violations. From the smallest violations to even the biggest violations. To overcome or overcome students who commit violations of these rules there must be techniques or solutions so that students become more disciplined individuals and obey school rules, so as to create conditions that are orderly and in accordance with applicable norms in the school environment. Rules must be obeyed by all members of the school, especially students because the aim is to provide someone with guidelines that have been approved in certain situations. At SMP Negeri 17 Surabaya, there are written rules for students regarding student discipline. These regulations have been classified according to type, iaiku mild, moderate and severe regulations. Although the rules are written, they are still violated by students. With these conditions, we want to find modern technology to overcome this problem.